PENGARUH PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA - Dewi, Esti Utami; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (Universitas Tanjungpura, 2024)
This study aims to determine student learning outcomes by applying the Teams Games Tournament model in class X at SMA Islam Bawari Pontianak. The research method used is an experiment in the form of Quaisy Experimental Design with a quantitative approach. The data sources in this study were students of class X IIS 3 who totaling 34 students as the experimental class and students of class X IIS 4 which amounted to 33 students as the control class. The technique used is direct observation technique and measurement technique using tools, namely observation sheets and test sheets. After the post test and measurements were carried out, it was found that the average score of the control class students was 32.15 while the average value of the students in the experimental class was 53.32. The results of the T test obtained a significance value of 0.00 0.05, so there were differences in learning outcomes. students in the control class and the experimental class. Based on the results of the Effect Size test obtained 2.25, which means that ES 0.70 is high. Based on this research, there are differences in student learning outcomes using the teams games tournament model with students using the inquiry model in geography learning class X Bawari Islamic High School Pontianak.